Estudos de modelagem molecular para previsão In Silico dos prováveis metabólitos de fase I de flavonóides - Sousa, Mariana Côrtes de (2012)
Flavonoids are an important class of natural products candidate drugs, and low molecular weight polyphenols, widely distributed throughout the plant kingdom. Investigations on its activities over the past 30 years, demonstrated a potential to prevent several diseases, among them cardiovascular diseases, inflammatory disorders, viral infections, diabetes and neurological disorders, in addition to its known antioxidant. The family of cytochrome P450 (CYP) is composed of monooxygenases, which play a crucial role in the metabolism of endogenous and exogenous substances, and participates in the metabolism of flavonoids. In this paper we describe the application of a methodology for exploring combined in silico prediction of sites of metabolism of quercetin, rutin, naringin and naringenin, found in abundance in nature. A methodology used was ligand based drug design (LBDD) to predict the sites of metabolism (SOM) and the program MetaPrint2D most likely estimate of the metabolites, combined with the method structure based drug design (SBDD) by using molecular docking and energy minimization, to predict the interaction of quercetin, rutin, naringin and naringenin with the isoforms CYP2C9 and CYP1A2. Metabolites were found several Phase I with catalytically active distance (<5 Å) and interaction sites described in the literature, with hydroxylation reactions of aliphatic, aromatic hydroxylation, dealkylation and O-dealkylation. The proposed in silico metabolic hydroxylation at the position corresponding to the C3' were consistent with studies in vitro and in vivo experiments described in the literature for naringin and naringenin. Amino acids of the active site of CYP isoforms have been identified as important in the positioning of the flavonoids quercetin, rutin, naringin and naringenin toward the heme, confirming the involvement of these isoforms in the metabolism of flavonoids.